STM fingerprint of molecule-adatom interactions in a self-assembled metal-organic surface coordination network on Cu(111) - Björk, Jonas; Matena, Manfred; Dyer, Matthew S.; Enache, Mihaela; Lobo-Checa, Jorge; Gade, Lutz H.; Jung, Thomas; Stöhr, Meike; Persson, Mats (Physical chemistry, chemical physics, 2010)
A novel approach of identifying metal atoms within a metal-organic surface coordination network using scanning tunnelling microscopy (STM) is presented. The Cu adatoms coordinated in the porous surface network of 1,3,8,10-tetraazaperopyrene (TAPP) molecules on a Cu(111) surface give rise to a characteristic electronic resonance in STM experiments. Using density functional theory calculations, we provide strong evidence that this resonance is a fingerprint of the interaction between the molecules and the Cu adatoms. We also show that the bonding of the Cu adatoms to the organic exodentate ligands is characterised by both the mixing of the nitrogen lone-pair orbitals of TAPP with states on the Cu adatoms and the partial filling of the lowest unoccupied molecular orbital (LUMO) of the TAPP molecule. Furthermore, the key interactions determining the surface unit cell of the network are discussed.